Azopyridine‐Containing Three‐arm Star Compounds with Aggregation‐induced Fluorescence. Issue 19 (10th August 2018) - Chen, Yinjie; Feng, Xing; Sun, Zhicheng; Wang, Dan; Yang, Tao; Zhao, Ziyuan; Li, Luhai; Wang, Xiaogong; Yu, Haifeng
Abstract: Three‐arm star azopyridinium salts self‐organize into various morphologies in water/organic mixed solvents. Interesting AIE and self‐assembling features are observed due to the strong interaction of the azopyridinium moieties with the highly polar H2 O molecules causing the salts to aggregate, which restricts the molecular motion and induces the fluorescence. Abstract : You′re a star ! Three‐arm star azopyridinium salts self‐organize into various morphologies in water/organic mixed solvent, and an interesting AIE feature is observed due to the strong interaction of the azopyridinium moieties with the H2 O molecules causing the salts to aggregate restricting the molecular motion.